Disability Education as a Missing Dimension in Community Development Practice in Kwa-Zulu Natal Province, South Africa - Zimkitha Mahlungulu; Edmore Ntini (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
This paper acknowledges the inadequacies in current community development practices, particularly regarding disability education in the rural areas of Kwa-Zulu Natal. It contends that a transformative integration of community education centred on disability is imperative for improving practice in this field. Community development often marginalises communities by persistently excluding them and inadequately addressing the integration of essential themes such as disability. Employing a qualitative methodology, this study analyses existing literature. The findings indicate that many community development initiatives predominantly emphasise health, economic activities, and gender-related issues while systematically overlooking other critical themes that are disability-related. Consequently, the study advocates for enhancing community development practices. Specifically, it recommends formally recognising Disability Studies as a distinct academic discipline within higher education institutions in the Kwa-Zulu Natal province to facilitate grassroots solutions to community challenges.